Efficacy of sinecatechins 10% as proactive sequential therapy of external genital warts after laser CO2 ablative therapy: The PACT study (post-ablation immunomodulator treatment of condylomata with sinecatechins): a randomized, masked outcome assessment, multicenter trial. (February 2019) - Puviani, Mario; Galluzzo, Marco; Talamonti, Marina; Mazzilli, Sara; Campione, Elena; Bianchi, Luca; Milani, Massimo; Luppino, Ivano; Micali, Giuseppe
External genital warts (EGW) are the most common viral sexually transmitted infection. Ablative treatments like cryotherapy, curettage, and CO2 laser therapies offer rapid onset of effect, fast clearance, and reduction of virus load. However, these procedures are associated with high recurrence rates (RRs) ranging from 20% to 77% in the short and medium terms and do not provide sustained clearance. After laser therapy removal of EGW, an RR up to 77% has been reported. Topical sinecatechins (TS) 10% is a patient-applied regimen for the treatment of EGW with a low RR (<6.5%) at three months after completion of the therapy in the pivotal trials conducted so far. Sinecatechins can be considered a suitable proactive sequential therapy (PST) after ablative strategies to obtain a low RR. So far, no prospective data are available regarding the efficacy of sinecatechins 10% as PST. We evaluated the efficacy and tolerability of TS 10% ointment applied twice daily in subjects with "difficult to treat" EGW after CO2 laser ablative treatment in a prospective controlled trial. A total of 87 subjects (76 men and 11 women; mean age 42 years) were enrolled in this three-month masked outcome assessment parallel group trial with imbalanced randomization allocation (2:1). One week after a successful CO2 laser treatment, 60 subjects were randomized to TS 10% treatment and 27 subjects to no treatment (control group: ConTRol (CTR); no sequential therapy). All patients had a history of an average of 4.5 previous ablative treatments in the last 12 months due to recurrent EGW. Mean (standard deviation) baseline number of treated lesions was 6.5 (2.7). One subject in the TS arm dropped out due to burning sensation after the application of the product. Therefore, 86 subjects completed the study. After three months, in the TS group, three subjects presented new EGW lesions (RR: 5%) on treated sites. In the CTR group, eight subjects presented new EGW lesions (RR: 29%) on treated sites (p = 0.0024; odds ratio: 0.16; 95% confidence interval: 0.04–0.68). In the TS group, 34 subjects (56%) reported mild to moderate erythema or burning sensation at the application site. In this prospective multicenter trial, the use of TS 10% as PST after ablative treatment with CO2 laser was associated with a lower recurrence rate of new EGW lesions in the short term in comparison with the control group. Comparative larger trials are warranted to evaluate the role of this approach as PST (Trial Registration Number: ISRCTN44037479).